7-Dimethylamino-2-phenyl-1,2,4-triazolo[1,5-a][1,3,5]triazin-5-amine methanol solvate. - Dolzhenko, Anton; Tan, G.; Koh, L.; Woo, S.; Chui, W. (Blackwell Munksgaard, 2008)
7-Dimethylamino-2-phenyl-1,2,4-triazolo[1,5-a][1,3,5]triazin-5-amine crystallized with one molecule of methanol to give the title compound, C12H13N7CH3OH. The triazolo[1,5-a][1,3,5]triazine heterocyclic core is essentially planar as are both amino groups that are involved in -electron delocalization with the triazolo[1,5-a][1,3,5]triazine nucleus. The methyl groups of the dimethylamino fragment are involved in the formation of weak intramolecular C-H...N hydrogen bonds with the N atoms of the heterocyclic system. The crystal packing is stabilized by intermolecular N-H...N hydrogen bonds between the triazolo[1,5-a][1,3,5]triazine molecules. The methanol solvent molecule also participates in the formation of the crystal structure via intermolecular O-H...N, N-H...O and weak C-H...O hydrogen bonds, linking the layers of triazolo[1,5-a][1,3,5]triazine molecules.